The role of the laboratory in treatment with new oral anticoagulants. (30th June 2013) - Baglin, T.
Summary: Orally active small molecules that selectively and specifically inhibit coagulation serine proteases have been developed for clinical use. Dabigatran etexilate, rivaroxaban and apixaban are given at fixed doses and do not require monitoring. In most circumstances, these drugs have predictable bioavailability, pharmacokinetic effects, and pharmacodynamic effects. However, there will be clinical circumstances when assessment of the anticoagulant effect of these drugs will be required. The effect of these drugs on laboratory tests has been determined in vitro by spiking normal samples with a known concentration of active compound, or ex vivo by using plasma samples from volunteers and patients. Data on the sensitivity of different reagents are now available, and so guidance as to the effect and interpretation of a test result is now possible. Laboratories should be aware of the sensitivity of their own assays to each drug. This may be achieved by using appropriate calibrated plasma samples.